The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1155/2011/968753
|View full text |Cite
|
Sign up to set email alerts
|

Subliminal Cues While Teaching: HCI Technique for Enhanced Learning

Abstract: This paper presents results from an empirical study conducted with a subliminal teaching technique aimed at enhancing learner's performance in Intelligent Systems through the use of physiological sensors. This technique uses carefully designed subliminal cues (positive) and miscues (negative) and projects them under the learner's perceptual visual threshold. A positive cue, called answer cue, is a hint aiming to enhance the learner's inductive reasoning abilities and projected in a way to help them figure out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…For a computerized quiz, Chalfoun and Frasson used subliminal messages to support learning solution strategies. Using subliminal messages resulted in 44 % less errors [3,4].…”
Section: Terminology and Related Workmentioning
confidence: 99%
“…For a computerized quiz, Chalfoun and Frasson used subliminal messages to support learning solution strategies. Using subliminal messages resulted in 44 % less errors [3,4].…”
Section: Terminology and Related Workmentioning
confidence: 99%
“…Examples of research include subliminal cueing in support of online help in a desktop-computer text-editing task application (Wallace, Flanery, & Knezek, 1991), just-in-time memory support using subliminal cues delivered in a head-mounted display (DeVaul et al, 2003), application in a tutoring system (Chalfoun & Frasson, 2011), and aid for visual search tasks (e.g., McNamara, Bailey, & Grimm, 2008;Bailey, McNamara, Sudarsanam, & Grimm, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In another study [13], visual masking was applied in the context of a virtual tutoring system. The results showed that subliminal cueing elicited better performances as well as better affective states throughout the lesson.…”
Section: Related Workmentioning
confidence: 99%
“…To briefly sum up, subliminal stimulation seems to be suitable for a variety of uses in concrete scenarios as those of memory retrieval [9] and problem solving [13] to bias decisionmaking in selection behavior [5,16] and navigation tasks [4]. In the specific context of symbiotic systems, such potential can be exploited to assist the user during critical phases or to manage his interaction without interrupting the task at hand [3] or generating mental workload [8,9].…”
Section: Related Workmentioning
confidence: 99%